ACI‐24 vaccine in adults with Down syndrome: Human: Putative therapeutic results for Alzheimer's and related dementias. (7th December 2020) - Rafii, Michael S; Mobley, William C; Skotko, Brian G.; Sabbagh, Marwan N.; Burke, Anna D.; Yuan, Shauna; Rissman, Robert A.; Chavez, Ronelyn; Delpretti, Saskia; Sol, Olivier; Beth, Greg; Gray, Julian JG; et al.
Abstract: Background: Individuals with Down syndrome (DS) are at increased risk for developing Alzheimer's Disease (AD) with 100% exhibiting amyloid pathology by age 40, making approaches targeting beta‐amyloid a rational strategy for the prevention of dementia. ACI‐24 is a liposomal vaccine eliciting polyclonal anti‐Aβ antibodies in a T‐cell independent manner. In this study, the safety, tolerability and immunogenicity of ACI‐24 in adults with DS are being tested. Methods: This is a sequential, dose‐escalating, placebo‐controlled, phase 1b study testing the safety and efficacy of ACI‐24 in two cohorts with 8 individuals each. Cohort 1 (ACI‐24 300μg or placebo) was followed by cohort 2 (ACI‐24 1000μg or placebo) each comprised of 6 active and 2 placebo‐treated participants. Each participant received 7 subcutaneous injections of ACI‐24 or placebo over 12 months, followed by a 12‐month safety follow‐up period. Participants are non‐demented DS individuals (25 to 45 yrs), able to complete study‐related procedures with a reliable study partner. Primary endpoints assess the safety and tolerability, including adverse events and other safety measures as well as the induction of anti‐Aβ antibody titers in serum. Secondary objectives explore the effect of ACI‐24 on cognition and behavior (Brief Praxis Test, Clinical Global Impression of Change, Vineland II Adaptive Behavior Scale, Neuropsychiatric Inventory and selected measures of the CANTAB), standard AD biomarkers, including Aβ and tau levels in plasma and/or CSF when available; T‐cell activation; and the effect on whole brain, ventricular and hippocampal volumes. Results: Sixteen participants were randomized into two study cohorts: cohort 1 (n=8; mean age 34.1 yrs) and cohort 2, (n=8, mean age 31.1 yrs). The majority of participants are Caucasian. The study population also has a high prevalence of obesity (mean BMI = 39.6). The safety and tolerability have been good to date, with no reported dropouts, serious adverse events or MRI abnormalities. Conclusion: The recruitment of this world's first clinical study using an anti‐Aβ vaccine (ACI‐24) in a DS population is now complete and has shown a good safety and tolerability to date. It represents a critical advance in developing potential therapies for the prevention of AD dementia in this at‐risk population.